Real‐Time Objective Evaluation of the Ischemic Stroke through pH‐Responsive Fluorescence Imaging. Issue 9 (31st January 2023) - Yao, Shasha; He, Chengbin; Yuan, Pengcheng; Xu, Xiaodan; Zhou, Xiaoxuan; Shen, Liyin; Hu, Qiuhui; Slater, Nigel K. H.; Sun, Wenjing; Shen, Youqing; Hu, Hongjie; Tang, Jianbin
Abstract: A rapid and comprehensive assessment of ischemic stroke (IS) is critical for clinicians to take the most appropriate treatment. Currently, IS assessment is mainly carried out by computed tomography and magnetic resonance imaging in combination with observing the clinical symptoms and inquiring about contraindications. However, they cannot diagnose pathological conditions and judge the microenvironment in real‐time. Near‐infrared fluorescence imaging has advantages for IS imaging, such as high sensitivity, high spatiotemporal resolution, and straightforward real‐time operation. Herein, a pH‐responsive fluorescent liposomal probe (BOD@Lip) is prepared for in vivo real‐time visualization of the degree of IS based on the different acid microenvironments in the progression of the disease. The fluorescence imaging with BOD@Lip shows the degree of IS, and the correlation between fluorescence signals and the neurological deficit scores is established for the first time. This work provides a new method to objectively evaluate the degree of IS through a visualized route and a new insight into the relationship between the acidic microenvironment and the progression of IS. Abstract : Schematic illustration of the pH‐responsive near‐infrared fluorescent probe (BOD@Lip) for in vivo real‐time visualization of the degree of ischemic stroke is based on the different acid microenvironments in the progression, and the correlation between fluorescence signals and the neurological deficit scores is established.